Aumento gengival associado à ciclosporina em transplantados renais no HUSM - Wentz, Luiz Augusto (2010)
Background: Gingival enlargement (GE) is a frequent finding in cyclosporin users. The mechanisms of this association are not totally known and point out to a multifactorial model, with dose and associations with calcium channel blockers. Novel immunosuppression protocols are adjusting for drugs and dosages. Aim: This study aimed at investigating the prevalence and severity of gingival enlargement in renal transplanted individuals under cyclosporin and possible associations with clinical and pharmacological findings. Methods: With a cross- sectional design, 63 renal transplanted patients under cyclosporin therapy from the University Hospital of the Santa Maria Federal University were examined. Demographic, pharmacological and periodontal variables were assessed. Data analysis, independent sample t test and chi square were used to compare means values of different variables, comparing groups with or without gingival enlargement. Results: A response rate of 86,30% was achieved. In total, 40% of the patients presented some degree of GE. Eleven presented scores >10% and only 5 presented scores of 30%. Mean value for GE was low (6,79±15,83). Patients under nifedipine presented higher prevalence of GE, without reaching statistical significance. Mean values for serum levels of CsA were 3,20±0,94 mg/kg/day and 156,12±162,75 ng/ml, respectively. No statistically significant differences among individuals with or without GE was obtained relating to the use of nifedipine and/or none/verapamil. Conclusion: A lower prevalence and severity of GE was found in relation to previous studies, independent to the drug association.